KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA SEKOLAH - Dace; Ihsan, Muzhir (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
This study aims to describe the principal's leadership in improving school performance. This study uses a qualitative descriptive approach, and the type of research used is literature. The results of the study conclude that the principal's leadership in improving school performance can be done through strategic steps by the principal by involving teachers in every decision. In addition, it is also necessary to carry out a program to improve the quality of learning. Personally, a school principal must also be able to actively establish internal communication between school equipment and establish joint external communication with students and parents. Furthermore, school principals also need to increase the enthusiasm of teachers in planning and implementing each policy and program that has been planned. The principal's strategic steps need to be based on mutual trust and commitment. The role of school principals who use a transformational leadership model will have a number of policies that are not only intended to respond to current interests but also look far into the future. Transformational leadership patterns as a leadership model that can be a master key in efforts to improve school performance as educational service providers.